Pulsed reverse electrochemical synthesis of Ag-TiO2 composites from deep eutectic solvents: Photocatalytic and antibacterial behaviour - Ionela-Cristina Petcu; Raluca Negrea; Ana T.S.C. Brandão; Cosmin Romanitan; Oana Brincoveanu; Nikolay Djourelov; Iuliana Mihalache; L. Monica Veca; Gabriela Isopencu; Carlos M. Pereira; Liana Anicai; Cristina Busuioc; et al. (Applied Surface Science Advances)
This study presents an environmentally friendly approach for synthesis Ag-TiO2 composite using pulsed reverse current (PRC) electrodeposition from green electrolytes, specifically deep eutectic solvents (DESs). The combination of PRC and DESs offers better control over nanoparticle synthesis while eliminating the need for toxic or expensive precursors, representing a significant advancement in sustainable nanomaterial synthesis. Different electrochemical parameters were adjusted, and their influence on the structure and morphology of the composite was investigated using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). TEM analysis revealed that silver nanoparticles (Ag NPs) are attached to TiO2 nanopowder, with the coexistence of TiO2 and Ag further confirmed by XRD and XPS. The recorded UV–Vis diffuse reflectance spectra (DRS) displayed a broad peak in the range of 400 – 650 nm, associated with the localized surface plasmon resonance (LSPR) of Ag NPs on the semiconductor’s surface. The photocatalytic activity of TiO2 nanopowder and Ag-TiO2 composite was evaluated based on the degradation of methyl orange (MO) dye under UV and visible light illumination. Our findings clearly demonstrated that the incorporation of Ag improved the photocatalytic efficiency. The mechanism of MO dye degradation was explored by using various scavengers, revealing that superoxide radicals (•O2−) play a dominant role. Furthermore, the incorporation of Ag NPs significantly enhanced the antimicrobial activity of the oxide against both Gram-positive (B. subtilis) and Gram-negative (E.coli) strains.